Propuesta de un plan para la gestión de residuos sólidos en el hospital jerusalén - la esperanza 2016 - Ordoñez Abanto, César Augusto (2016)
We presented a proposal of a plan to management of solid waste in the Jerusalem hospital - La Esperanza 2016, in Where It evaluated the management of the solid waste in the Jerusalem hospital based in the Technical Norm of Health No. 096 - Ministry of Health / DIGESA V .01, taking into account the criteria established for the preparation of a plan of handle of hospitable waste designed in basis to the study of characterization of solid waste made of agreement to the norm in quotation. the plan presented two alternatives for the end treatment of the hospitable solid waste, the first by Means of a Company Prestadora of Services of Recollection of Solid Waste (EPS-RS) and the second by means of the purchase of an autoclave with grinder integrated; which when being evaluated with the incremental attains costs determine that the first proposal profitable is, however the second is profitable on a long-term basis and with a lower investment by the state by what this last was taken in account, later attains identify the dangers and Risks to the health as well as past the main appearances and environmental impacts that would generate in the processes and sub processes of the operation of the plan to hospital solid waste management, Which are mitigated by Means of corrective actions, Attaining like this present a proposal of a plan to management of Solid Waste in Jerusalem hospital - La Esperanza 2016